Patterns of Investing into Business R&D in South Africa - Neo Molotja; Saahier Parker; Precious Mudavanhu (Foresight and STI Governance, 2019)
The paper explores the patterns of business investment in research and development (R&D) using evidence from companies in South Africa, in comparison with indicators for a number of other countries. This study covers the period 2006–2016, the studied companies were grouped by the amount of R&D expenditures (BERD), the number of reports on research performance for the first and last years of monitoring. A typical characteristic of private sector R&D activities is the uneven distribution of resources in space and time. The major financial and other assets are concentrated within few large companies from a limited number of industries, while the majority of small and medium-sized enterprises invest in R&D projects only sporadically, for a period of no more than two consequential years. Firms that perform R&D for longer periods invest in R&D incrementally and remain more persistent than enterprises performing less R&D for shorter time periods. In view of the common nature of a number of patterns, these observations suggest different approaches to policies supporting R&D performance in the business sector not only in South Africa, but also in other countries.